2013
DOI: 10.1371/journal.pone.0079003
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine-to-Uracil Deamination by SssI DNA Methyltransferase

Abstract: The prokaryotic DNA(cytosine-5)methyltransferase M.SssI shares the specificity of eukaryotic DNA methyltransferases (CG) and is an important model and experimental tool in the study of eukaryotic DNA methylation. Previously, M.SssI was shown to be able to catalyze deamination of the target cytosine to uracil if the methyl donor S-adenosyl-methionine (SAM) was missing from the reaction. To test whether this side-activity of the enzyme can be used to distinguish between unmethylated and C5-methylated cytosines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Methylated cytosine is a dynamic modification not only because it is added and removed by enzymatic processes, but also because it can spontaneously deaminate and, therefore, mutate [15,16,17]. By contrast, spontaneous deamination of unmethylated cytosine is readily recognized by the DNA repair machinery and corrected.…”
Section: Introductionmentioning
confidence: 99%
“…Methylated cytosine is a dynamic modification not only because it is added and removed by enzymatic processes, but also because it can spontaneously deaminate and, therefore, mutate [15,16,17]. By contrast, spontaneous deamination of unmethylated cytosine is readily recognized by the DNA repair machinery and corrected.…”
Section: Introductionmentioning
confidence: 99%
“…At least one human APOBEC3 paralog (3A, but not 3G) indeed deaminates 5mC in DNA faster than AID [57], but the single murine APOBEC3 also discriminates against 5mC [52]. Some prokaryotic methyltransferases can catalyze deamination of Cs to uracils [58] and of 5mCs to thymines [59] in the absence of S-adenosylmethionine (SAM), but mammalian DNA methyltransferases are not known to catalyze this reaction, either in vitro or in vivo. Moreover, the implication of alternative deaminases does not explain the genetic data that implicate specifically Aid and not deaminases in general in DNA demethylation.…”
Section: Introductionmentioning
confidence: 99%
“…The results from amplicon sequencing showed that the mean methylation level was 60.4 ± 9.9% when the Sss I-remethylated DNA template was used, whereas the levels were 1.6 ± 2.5% and 29.8 ± 8.2% when the demethylated DNA template only or an equal mixture of remethylated and demethylated DNA, respectively, was used ( Figure 1C ). The 60% methylation level obtained from the use of the remethylated DNA indicated an incomplete methylation, possibly by insufficient Sss I enzyme activity or Sss I-catalyzed cytosine-to-uracil conversion in SAM deficient condition ( Bandaru et al, 1995 ; Zingg et al, 1996 ; Stier and Kiss, 2013 ). Nevertheless, the 30% methylation level acquired from the 1:1 mixed DNA template implied that the methylation frequencies of target CpGs at genomic regions were well-preserved even after the multiplex PCR and library preparation processes during TBPseq.…”
Section: Resultsmentioning
confidence: 99%